A view of 21st century healthcare industry and software quality improvement practices. (1st January 2011) - Nguyen, Tien D.; Guo, Hong; Naguib, Raouf N.G.; Wickramasinghe, Nilmini
In a rapidly expanding industry such as healthcare, information and communication technology is increasingly becoming a key role in supporting, maintaining and improving healthcare services. This paper discusses the impact and future development of software within the healthcare field. At the same time, it identifies the current state, challenges and solution of software quality improvement and assurance practices for this domain.